Pre-harvest glyphosate desiccation on barley seed quality (Research, Society and Development, 2021)
The experiment was conducted into two stages, the first being the barley seed production and application of glyphosate and the second the vigour tests in the laboratory. Both stages were performed at the Experimental Farm of Agrarian Sciences at Grand Dourados Federal University (UFGD). In field, four cultivars of barley was sowing being: BRS Cryst, BRS Kallibre, BRS Demeter, BRS Sampa. For desiccation, the glyphosate herbicide (480 g L-1 of active ingredient) was used, applied using a backpack sprayer at dose of 5 L ha-1. The experimental design used was randomized blocks, and each cultivar was divided into five replications, applying the herbicide in four of them leaving one without application for control. The application was made when seeds presented water content close to 50%. At second stage, eight evaluation were made being one at the day of glyphosate application, one, two, three, eight, ten and fourteen days after application and without application in natural physiological maturity. In each evaluation, sowing was performed according to Rules to Seed Analysis. The analyses were: First count,  percentage of germination,  germination speed index, mean germination time, mean germination speed, accelerated aging and synchronization index. Glyphosate has interfered negatively in the physiological maturation of barley seeds when the herbicide was applied in pre-harvest. The results obtained showed that there was an increase in seeds germination after 14 days of application, however, the means were significantly smaller in relation to seeds harvested at the point of physiological maturation without glyphosate application.